Sensory-friendly spaces for children with autism spectrum disorder (ASD) to stimulate learning environment / Mohamad Izzat Zulkanain and Md Azree Othuman Mydin - Zulkanain, Mohamad Izzat; Othuman Mydin, Md Azree (2019)
Autism Spectrum Disorder (ASD) is referred as a spectrum disorder because each individual has different symptoms, sensitivities and level of functioning. Each of the autistic children’s sensory sensitivities differs from one to another. Specialized design of learning spaces for ASD children may unlock their full potential. Hence this research attempted to design sensory- friendly spaces for children with ASD to stimulate learning environment. The objectives of this research are in 3 folds; (1) to scrutinize the existing body of knowledge to ascertain relevant criteria exist to design space for ASD; (2) to evaluate three centres for children with ASD in relation to the body of knowledge examined; (3) to propose an inclusive design of spaces for children with ASD. Three case study are chosen for this study that are Calvary Victory Centre (Johor), Penawar Special Learning Centre (Johor) and National Autism Society Malaysia (NASOM) One Stop Centre (Selangor). Then, six components are identified to be considered in the design of the spaces and four stimuli consideration are identified that is needed to be implemented. So, designing a space that provide conducive environment for these children to use any of their senses comfortably, it may lead to effectiveness in learning process.